Mineral texture and composition of magnetite in the Sahavaara IOCG deposit, Pajala area : a mineral processing approach - Abongwa, Paul Wanka (2009)
Stora Sahavaara is one of several iron (Cu-Au) deposits of economic potential in the Pajala-Kolari area and it is currently developed for mining by Northland Resources Inc. These deposits are hosted by 2.3-2.0 Ga Karelian greenstones and occur as magnetite-rich lenses at certain stratigraphical positions and often in association with carbonate rocks. They contain various amounts of skarn minerals with serpentine, pyroxene, and amphibole as the most important gangue minerals. The Stora Sahavaara iron occurrence was previously considered as belonging to a broad group of magnetite-dominated, Ca-Mg- and Mg-silicate skarn-hosted deposits, which occur throughout northern Sweden, within a Karelian volcano-sedimentary domain. Several deposits considered to be of the same type also occur and have been well studied in the Finnish part of the Lappland, in the Kolari district. These deposits, which are interpreted to be epigenetic Fe-Cu + Au deposits, occur within the same structures as the Stora Sahavaara deposit. They are suggested to belong to the increasingly important group of iron- oxide-copper-gold (IOCG) deposits. A characteristic feature of the Stora Sahavaara magnetite is the high Mg content of its concentrate which is suggested to be lattice bound. In some cases the recovery (magnetite) is poor, or the concentrates are not clean, which is clearly indicated by a high SiO2 content in the concentrate. Also, significant inclusions/intergrowths of sulphides in magnetite grains could cause the final iron ore concentrate to have high S content, for example. Alternatively, the grade may be lower than predicted due to silicate or other gangue carrying finely disseminated magnetite in some textural ore types. The general purpose of this work is to apply the mineralogy and geology of the Stora Sahavaara deposit in order to better understand the metallurgical processing characteristics of the ore. For the mineral processing of the ore and the properties and quality of the final products, the texture of magnetite, its ...